Bacterial and parasitic contamination of raw vegetable in Jember regency, Indonesia : potential risk for food-borne diseases - Diana Chusna Mufida; Elvia Rahmi Marga Putri; Dini Agustina; Enny Suswati; Muhammad Ali Shodikin; Yunita Armiyanti; Bagus Hermansyah; Wiwien Sugih Utami; Angga Mardro Raharjo (International Journal of Public Health Science (IJPHS), 2022)
A raw vegetable is one of the transmission factors in human food-borne infection. Contamination might start from the plantation, distribution, until at serving time in the dining table. A higher level of contamination will increase the risk of food-borne illness. The study aims to determine bacteria and parasite contamination in some raw vegetables that people usually consume in Jember Regency, East Java, Indonesia. In this study, we collected raw vegetable from eight traditional markets. We chose randomly at each market five samples of vegetables that usually directly consumed, like lettuce, tomato, cabbage, basil, long bean, and cucumber. Pathogens we identified limited on bacteria and parasite like helminth and protozoan group. This study showed that 91% contaminated by E. coli, 84% by Staphylococcus aureus, and 79% contaminated by Vibrio cholerae. Besides bacteria, 36% of samples contaminated by the helminth group, and protozoa contaminated 27%. The most vegetables contaminated was lettuce, even in bacterial or parasitic contamination. This study concluded that there is contamination in raw vegetables usually directly consumed in Jember Regency. It will be a potential risk factor for food-borne illness in the future.